Prognostic, clinical, and therapeutic importance of RANTES‐CCR5 axis in hepatitis A infection: A multiapproach study. Issue 6 (8th October 2020) - Baruah, Vargab; Tiwari, Diptika; Hazam, Rajib Kishore; Bose, Moumita; Bujarbaruah, Dipankar; Saikia, Anjan Kumar; Kar, Premashish; Dutta, Sangit; Bose, Sujoy
Abstract: Fulminant hepatic failure (FHF) is a lethal manifestation of hepatitis A virus (HAV) infection, whose underlying mechanisms are poorly understood. We aimed to evaluate the importance of the modulation of the RANTES‐chemokine receptor type 5 (CCR5) signaling axis and its immunomodulatory effects in directing hepatitis A disease pathogenesis using an in silico, in vitro and patient cohort‐based approach. In silico interaction studies were performed using computation approaches with suitable software. Differential expression of relevant cytokines and immune cell markers were studied using real‐time quantitative reverse transcription PCR (qRT‐PCR), enzyme‐linked immunosorbent assay, and flow‐cytometry‐based methods. In the HepG2 cell line, we studied inflammatory responses and susceptibility to HAV infection following RANTES stimulation and antibody blockade of CCR5. The HAV‐VP3 region exhibited high interaction in CCR5: HAV complexes. RANTES levels were significantly increased in FHF cases. Reduced monocyte and T‐cell activation were observed in FHF cases. RANTES expression inversely correlated with viremia but positively correlated with proinflammatory responses. Hyper Th1‐biased immune responses, marked by high interleukin (IL)‐12/IL‐10 ratio were observed in FHF cases, which were also characterized by upregulated tumor necrosis factor‐alpha (TNF‐α) expression and reduced interferon‐gamma expression. In vitro, RANTES was protective against HAV infection but resulted in upregulated TNF‐α expression. Although viral load increased upon the regulation of inflammatory responses by CCR5 blocking, it was still significantly lower compared to control HAV‐infected cells. Our study suggests the importance of RANTES‐CCR5 signaling and linked‐immunomodulation in HAV disease pathogenesis, as well as highlights the utility of CCR5 antagonists as a risk‐reduction strategy in FHF patients. Our findings, therefore, have important implications for the management of high‐risk HAV infections. Highlights: Hepatitis A virus infection mediated significant RANTES expression in patients. Fulminant patients exhibited altered RANTES‐linked Th1‐biased immunomodulation. Supportive correlations were observed between immunomodulation and outcome. Immune responses were studied in RANTES‐stimulated, HAV‐infected HepG2 cell line. Inflammatory outcomes of protective RANTES could be regulated by CCR5 blocking.